Klebsiella pneumoniae as a Main Cause of Infection in Nishikigoi Cyprinus carpio (Carp) by Inadequate Handling - Oliveira, Renato Ventresqui; Peixoto, Pedro Gomes; Ribeiro, Douglas de Castro; Araujo, Marcelo Costa; Santos, Celso Tadeu Barbosa do; Hayashi, Carmino; Pedreira, Marcelo Mattos; Pelli, Afonso (Brazilian Journal of Veterinary Pathology, 2014)
Klebsiella spp. is a genus of the gram-negative Enterobacteriaceae family. They are found in many environments and are part of the natural microflora of soils, effluents and surface water and in some plants. Klebsiella spp. is an opportunistic agent and mainly attacks subjects hospitalized with severe diseases as well as many fragile animals. This paper reports the occurrence of Klebsiella pneumoniae infection in a nishikigoi carp, Cyprinus carpio, widely used as an ornamental fish in aquaria, for food, and for production of pituitary extracts for induction of reproduction. In a closed system used for the domestic cultivation of ornamental fish, a carp was found with an injury indicative of bacterial infection. A tissue sample from a lesion was triturated, plated on Blood Agar, and incubated at 37° C for 24 hours to confirm and isolate the possible pathogen. Biochemical tests were conducted to identify the strain based on manual methods described in the literature. In accordance with the phenotypic and biochemical tests conducted, Klebsiella pneumoniae was the organism present in the carp lesion.